Divine and demonic necessity in the Oresteia - Edsman, Carl-Martin (Scripta Instituti Donneriani Aboensis, 1967)
Aeschylus remains wholly within the context of the ancient religion. He forms his dramatical works with stern gravity and deep religiosity, so that a pervading piety is natural and there are no godless people. The archaic attitude of the poet appears not the least in his view of the departed. They are bloodless shadows without emotions or perceptions. But at the same time the murdered ones cry for vengeance, Nemesis rules over all and everything, and Dike looks after the right of the angered dead. The departed, therefore, have a dangerous power. When the earth has drunk the blood of a murdered person there is no turning back, even Zeus himself is then powerless. The entire Oresteia is concerned with the necessity and the problem of blood-revenge, with retributive justice, but also—one must add—with atonement. Even if one may never disregard Aeschylus’ historical background and his own particularity, the problems raised by the Oresteia are universally human and timeless. They may be expressed in different words in different times. But they are basic conditions of human existence.